Lion City : Singapore and the Invention of Modern Asia - Vasagar, Jeevan (London Abacus, 2022)
Jeevan Vasagar is a superb and evocative writer, and Lion City is a compelling, illuminating and personal history that will be regarded as the definitive book on Singapore - and one of the great city chronicles.
Including Index
Keywords: Singapore -- Economic history